Vitreous levels of Lipocalin-2 on patients with primary rhegmatogenous retinal detachment. - Georgios Batsos; Eleni Christodoulou; Georgios Vartholomatos; Petros Galanis; Maria Stefaniotou (PLoS ONE)
Purpose To measure vitreous levels of Lipocalin2 (LCN2) in patients with rhegmatogenous retinal detachment (RRD) and investigate potential association with presence of proliferative vitreoretinopathy (PVR). Materials and methods Collection of undiluted vitreous samples from 24 patients suffering from RRD and 10 control patients undergoing vitrectomy for: vitreomacular traction (VMT) (n = 2), idiopathic epiretinal membrane (iERM) (n = 6) and full thickness macular hole (FTMH) (n = 2). Quantitative analysis of LCN2 has been made with flow cytometry. Lens status, duration of symptoms, quadrants of detachment, as well as level of PVR, were assessed. Statistical analysis included Mann-Whitney test, Kruskal-Wallis test, t-test, Spearman's correlation coefficient and Fisher's exact test. Results Median LCN2 was significantly higher in the RRD group as compared to control (p<0.001). Within the RRD group there was a positive correlation between LCN2 and PVR grade (rs = 0.94, p<0.001). Median LCN2 was 35,759 pg/ml (IR = 55,347) in grade C PVR, 9,387 pg/ml (IR = 3721) in grade B, 4,917 pg/ml (IR = non computable) in grade A and 3,921 pg/ml (2132) in the no PVR group. Median LCN2 was also significantly higher in pseudophakic patients as compared to phakic patients (p = 0.007). LCN2 also correlates with the extend of detachment (≤2 vs >2 quadrants, p<0.001) as well as with duration of symptoms (rs = 0.87, p<0.001). After multivariate linear regression analysis, only PVR was independently related with LCN2 concentration. In particular, increased PVR grading was associated with increased LCN2 concentration (coefficient b = 2.97, 95% confidence interval = 1.89 to 4.67, p<0.001). Conclusion A positive correlation between vitreous levels of LCN2 and PVR grading reveals a potential role in the pathogenesis and progression of PVR. Further studies could elucidate if LCN2 could be a therapeutic target.